2011
DOI: 10.1039/c0cc05548d
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic CdSe QDs-decorated ZnO nanotubes: an effective photoelectrode for splitting water

Abstract: Arrays of ZnO nanorods (NRs) were successfully converted into nanotubes (NTs), used as photoelectrodes in photoelectrochemical (PEC) cells after their sensitization with CdSe quantum dots (QDs) and a strong correlation between the PEC performance and geometrical structure of ZnO NTs@CdSe(QDs) and ZnO NRs@CdSe(QDs) was established under the same conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Whereas, the wide band gap (3.2 eV) of TiO 2 material limits its practical application because it only can be excited with light of wavelength near or shorter than 385 nm. Other metal oxide semiconductors such as WO 3 , ZnO, BiVO 4 and so have been extensively studied for photo-electrochemical water splitting [2][3][4][5][6][7][8]. However, because of the difficulty in discovering a single semiconductor that is capable of splitting water into hydrogen and oxygen, efforts to develop and optimize semiconductors for independent water oxidation and reduction are more realistic [9].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the wide band gap (3.2 eV) of TiO 2 material limits its practical application because it only can be excited with light of wavelength near or shorter than 385 nm. Other metal oxide semiconductors such as WO 3 , ZnO, BiVO 4 and so have been extensively studied for photo-electrochemical water splitting [2][3][4][5][6][7][8]. However, because of the difficulty in discovering a single semiconductor that is capable of splitting water into hydrogen and oxygen, efforts to develop and optimize semiconductors for independent water oxidation and reduction are more realistic [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the intrinsic band gap of TiO 2 (3.2 eV) and high recombination rate of photogenerated electron-hole pairs are the main drawbacks limiting the future improvement of photochemical activity. Various attempts such as substitutional element doping [10][11][12] and surface modification with noble metal and semiconductor [13][14][15] have been successfully tried to overcome the two obstacles. Coupling a second narrow band-gap semiconductors with a more negative conduction band level can result in the vectorial transfer of conduction band electrons and valence band holes from one semiconductor to another.…”
Section: Introductionmentioning
confidence: 99%
“…CdS sensitized ZnO nanorod array shows a photocurrent densities of 23.7 and 15.8 mA cm À2 at a 0 V bias under the illumination of simulated sunlight and visible light, respectively [77]. CdSe sensitized ZnO nanotube shows~5 mA cm À2 at 0.35 V vs SCE [78]. Wang et al [79] reported double-sided CdS and CdSe quantum dot co-sensitized ZnO nanowire arrays yielding a photocurrent of~12 mA cm À2 at 0.4 V vs Ag/AgCl.…”
Section: Quantum Dot (Qd) Sensitizationmentioning
confidence: 99%